1990
DOI: 10.1002/bjs.1800770310
|View full text |Cite
|
Sign up to set email alerts
|

Pouch size: The important functional determinant after restorative proctocolectomy

Abstract: Sixty-seven patients with a J-shaped ileonanal pouch were studied over a 2-year period with regular recording of sphincter and pouch characteristics and analysis of their role in functional outcome. Although there was a 27 per cent permanent reduction in resting anal pressure (RAP) (P less than 0.001), two-thirds of the patients still had a RAP within the normal range. The mean(s.d.) pouch volume increased during the first year from 132(46) ml to 282(85) ml. RAP was not related to functional outcome and preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
2
3

Year Published

1990
1990
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 27 publications
4
31
2
3
Order By: Relevance
“…Some of this improvement in quality of life in the long term may be the result of increased coping mechanisms. 27 This series confirmed the findings of other large series showing a high level of patient satisfaction with pelvic pouches. 14,25 As it was for quality of life, this satisfaction was maintained over time.…”
supporting
confidence: 81%
“…Some of this improvement in quality of life in the long term may be the result of increased coping mechanisms. 27 This series confirmed the findings of other large series showing a high level of patient satisfaction with pelvic pouches. 14,25 As it was for quality of life, this satisfaction was maintained over time.…”
supporting
confidence: 81%
“…This scoring system, which has been used by several investigators, was designed to quantify overall functional results and is calculated by the simple addition of all arbitrary scores. 26,[52][53][54][55] The distance from the anal verge to the anastomosis in colonic J-pouch reconstruction has been reported to range from 1 to 8 cm, 7,[9][10][11]19,21,23 although the ideal anastomotic location for colonic J-pouch reconstruction has not been established. In a previous study, we tried to determine the level at which J-pouch reconstruction provides a functional advantage over straight anastomosis and found that colonic J-pouch reconstruction is indicated when the anastomosis is less than 8 cm from the anal verge, and is essential when it is less than 4 cm from the anal verge.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 32 were symptomatic and 28 needed treatment. The symptoms of retained inflamed mucosa are those of proctitis, including bleeding, burning and urgency 109,110 . Disordered evacuation with the frequent passage of small amounts of stool may also occur, and patients are at continuing risk of neoplastic transformation 111 .…”
Section: Retained Rectummentioning
confidence: 99%